Cephalometric evaluation of hyoid bone position in subjects with different vertical dental patterns - Soyoye, O; Otuyemi, O; Newman-Nartey, M (Nigerian journal of clinical practice, 2021)
Objective: This study investigated the relationship between hyoid position and vertical dental dimensions (overbite), and the influence of gender on the location of this bone. Methods: One hundred and seventy-four standardized lateral cephalometric radiographs were randomly selected from a pool of radiographs of patients seeking orthodontic treatment with ages ranging from 10 to 58 years. The subjects were divided into three groups according to their vertical dental dimensions (overbite) into reduced, normal, and increased overbite groups. The hyoid bone position was determined by four horizontal linear and three vertical linear line measurements. Associations between the position of the bone and different vertical dental patterns were analyzed using ANOVA and Tukey's multiple comparison analysis. Results: There was a progressive increase in the horizontal linear position of the hyoid bone parameters across the groups from the reduced through normal to increase overbite. Similarly, a statistical reduction in the vertical linear positions of the hyoid bone parameters was found across the groups from reduced overbite through normal overbite to increased overbite (P < 0.05). The vertical linear hyoid bone positions were located higher in the male than in female subjects. Tukey's multiple comparison analysis showed a highly statistically significant difference in the vertical linear hyoid bone positions between reduced and normal overbite groups and between reduced and increased overbite groups. Conclusion: The hyoid bone was positioned more antero-inferiorly and more postero-superiorly in subjects with reduced overbite and increased overbite, respectively.